Heusler Alloys Properties, Growth, Applications - Felser, Claudia; Hirohata, Atsufumi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book gives an overview of the physics of Heusler compounds ranging from fundamental properties of these alloys to their applications. Especially Heusler compounds as half-metallic ferromagnetic and topological insulators are important in condensed matter science due to their potential in magnetism and as materials for energy conversion. The book is written by world-leaders in this field. It offers an ideal reference to researchers at any level.
Theory of Heusler Compounds -- Properties -- Applications -- Heusler Alloy Films: Film Growth -- Heusler Alloy Films: Magnetic Properties -- Device Applications -- New Properties.
Keywords: Optical materials; Magnetism; Energy policy; Energy and state; Optical Materials; Magnetism; Energy Policy, Economics and Management